Book Reviews. Issue 2 (11th October 2018) - McGrath, Patrick; Klawitter, George; Griffin, Dustin
Abstract : 1) George Klawitter, Andrew Marvell, Sexual Orientation, and Seventeenth-Century Poetry, reviewed by Patrick McGrath 2) A.D. Cousins, Andrew Marvell: Loss and Aspiration, Home and Homeland in Miscellaneous Poems, reviewed by George Klawitter 3) Matthew C. Augustine and Steven N. Zwicker, eds., Lord Rochester in the Restoration World, reviewed by Dustin Griffin